The use of tensiomyography to evaluate neuromuscular profile and lateral symmetry in competitive female surfers - Gravestock, H. J.; Barlow, M (Advances in Skeletal Muscle Function Assessment, 2017)
The aim of this study was to determine the contractile properties and muscle stiffness to assess lateral symmetry in competitive female surfers. Fifteen competitive female surfers volunteered to participate in the study. Tensiomyography was used to derive maximum muscle belly displacement, and time delay duration of the Biceps Brachiis, Biceps Femoris, Deltoid, Gastrocnemius lateral head, Rectus Femoris, Tibialis Anterior, Triceps Brachii and Vastus Medialis. No significant differences between right and left limbs at in any of the tested muscles were observed (p > 0.05). Competitive female surfers showed that upper body muscles had the ability to generate force rapidly during contractions, while the lower body muscles generated force at a slower rate. Surf specific training seems to have had an influence on the contractile properties, and stiffness of these muscles. The neuromuscular profile provided here provides further nor-mative data to this unique population.